2012
DOI: 10.3109/03014460.2012.693199
|View full text |Cite
|
Sign up to set email alerts
|

Puberty as a life history transition

Abstract: This review connects Tanner's contributions to contemporary understanding of puberty as a process fundamentally driven by neuroendocrine maturation. It introduces the concepts of the 'hour-glass of puberty' and 'somatic strategy' as heuristic constructs. The 'hour-glass of puberty' describes the converging pathways of information flow influencing the timing of the neuroendocrine events of puberty and its ramifying consequences throughout the body. Somatic strategy refers to the pattern of sex-specific, adult b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 100 publications
1
46
0
Order By: Relevance
“…The start of puberty, which marks the end of childhood and the onset of adolescence, is a critical life history transition (Ellison et al, 2012). In mammals, independence from parental care and dispersal typically occur during the peripubertal period, but the timing of independence and dispersal varies by species, season, sex, and even individual factors.…”
Section: Puberty As a Life History Transitionmentioning
confidence: 99%
“…The start of puberty, which marks the end of childhood and the onset of adolescence, is a critical life history transition (Ellison et al, 2012). In mammals, independence from parental care and dispersal typically occur during the peripubertal period, but the timing of independence and dispersal varies by species, season, sex, and even individual factors.…”
Section: Puberty As a Life History Transitionmentioning
confidence: 99%
“…A variety of permissive signals may converge on GnRH neurons, including photoperiod (i.e. melatonin), energy balance or metabolic (i.e., body fat, leptin), and psychosocial signals (Ellison et al, 2012; Sisk and Foster, 2004). These signals are mediated by the general excitatory and inhibitory neurotransmitters, glutamate and GABA, respectively (Parent et al, 2005).…”
Section: Gonadal Steroid Hormonesmentioning
confidence: 99%
“…The adolescent transition is a particularly useful time to consider energetic dynamics, as during puberty investment in linear growth is first increased (the adolescent growth spurt) and then terminated. Meanwhile, investment in reproduction, manifested in females as the development of primary and secondary sexual characteristics and an increased metabolic priority given to energy storage as fat, increases as investment in growth subsides [18]. For instance, prior work from our group demonstrated that, in this participant sample, younger individuals prioritize lean mass, even at the expense of fat, while older individuals prioritize the fat deposits critical for reproductive success [39].…”
Section: Discussionmentioning
confidence: 99%
“…These pubertal girls are undergoing the adolescent transition and the accentuated energy demands of the growth spurt. During this time, individuals are increasing energy allocation to linear growth as well as differentially investing in tissue important to reproductive capacity, such as muscle and fat [18]. The immune system also undergoes changes during adolescence, though these are less well-understood.…”
Section: Background and Objectivesmentioning
confidence: 99%